Polyphonic Music of the Fourteenth Century vols. XIII, XV, XXI and XXII - Fischer, Kurt von; Bent, Ian 1938-; Greene, Gordon K. (Monaco Éditions de l'Oiseau-lyre, 1982)
This important series, the result of thirty-five years work, is made specially for universities, libraries and scholars. Containing the corpus of fourteenth-century polyphony—well over 2000 pieces—it is an indispensable collection for all serious students and performers.
vol. XIII: Italian sacred and ceremonial music; vol. XII: French secular music; vol. XXI: French secular music: Virelais; vol. XXII: French secular music: Ballades and canons
Keywords: Middle Ages (500-1400); Vocal music; Song; Ballade; Canon; Italy; France